Use of fascial grafts as an interface in flap prefabrication: An experimental study - (:unkn) unknown (Lippincott Williams and Wilkins, 1999)
An experimental study was conducted to investigate whether a fascial graft can be used as an interface between a vascular pedicle and target tissue to augment tissue survival in a prefabricated flap. Thirty-six male Sprague-Dawley rats were divided into three experimental groups according to the type of the recipient bed prepared for the vascular implantation. The left saphenous vascular pedicle was used as the vascular source. A 9 x 9-cm inferiorly based peninsular abdominal flap was elevated in each animal. In group I, the pedicle was tacked beneath the abdominal flap, in which the epigastric fascial layer was untouched. In group II, a 3 x 5-cm graft of epigastric fascia was harvested from the abdominal flaps under loupe magnification. The graft was sutured back into its original position after a 180-deg rotation. The vascular pedicle was then implanted just beneath the center of the fascial graft. In group III, the same size of epigastric fascia was removed in the same manner as group II, exposing the subcutaneous layer for pedicle implantation. Four weeks later, abdominal flaps were raised as island flaps connected only to the saphenous pedicle and were sutured in place. Flap viability was assessed visually on day 7. Overall, the ultimate flap survival in group I was the largest, with some necrotic areas at the periphery of the flaps. In group II, flap survival was typically centralized over the fascial graft, and crescent-shaped necrosis was noted superiorly. In group III, an almost linear pattern of survival overlying the vascular pedicle was observed. The mean surviving flap area of group I (12.13 ± 1.615 cm2) was statistically greater than that of group II (8.83 ± 0.663 cm2, p < 0.001) and group III (6.3 ± 0.815 cm2; p < 0.001). There was a statistically significant difference between the mean flap survival in groups II and III (p < 0.001). Vascular arborization was examined by microangiography, and specimens were processed for histological staining. In group II, vascularization was distributed in a larger area along the fascial graft in comparison with limited vascularization around the pedicle in group III. In this study it was revealed that the interposition of a fascial graft as an interface between the vascular source and the target tissue seems to increase the size of the prefabricated flap.